2023
DOI: 10.3390/cells12060931
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of miR133b in a NEO100-Based Formulation Induces a Healing Response in Spinal Cord-Injured Mice

Abstract: Despite important advances in the pre-clinical animal studies investigating the neuroinhibitory microenvironment at the injury site, traumatic injury to the spinal cord remains a major problem with no concrete response. Here, we examined whether (1) intranasal (IN) administration of miR133b/Ago2 can reach the injury site and achieve a therapeutic effect and (2) NEO100-based formulation of miR133b/Ago2 can improve effectiveness. 24 h after a cervical contusion, C57BL6 female mice received IN delivery of miR133b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…We previously reported the efficacy of miR133b in healing the injured spinal cord when administered either intravenously [ 13 ] or intranasally [ 14 ] 24 h after injury. To better understand the dynamics of miR133b in a contusive type of injury, in this study we aimed to determine the changes in the endogenous level of miR133b at (a) the lesion site, (b) proximal and distal sites of the lesion, (c) pre-frontal cortex, and (d) off-targets, such as spleen and lungs, at different time points after SCI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported the efficacy of miR133b in healing the injured spinal cord when administered either intravenously [ 13 ] or intranasally [ 14 ] 24 h after injury. To better understand the dynamics of miR133b in a contusive type of injury, in this study we aimed to determine the changes in the endogenous level of miR133b at (a) the lesion site, (b) proximal and distal sites of the lesion, (c) pre-frontal cortex, and (d) off-targets, such as spleen and lungs, at different time points after SCI.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that administration of miR133b, either intravenously [ 13 ] or intranasally [ 14 ], in combination with NEO100, a purified version of perillyl alcohol, targeted the microenvironment of the fibrotic scar, leading to improved healing and motor function in a mouse model of cervical contusion injury. While these studies highlighted the beneficial role of miR133b when administered 24 h after spinal cord injury, its local dynamics in the lesion, as well as in other areas of the spinal cord, are not well-known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations